User experience innovation user centered design that works - Kraft, Christian (Apress, 2012)
User Experience Innovation is a book about creating novel and engaging user experiences for new products and systems. User experience is what makes devices such as Apple's iPhone and systems such as Amazon.com so successful. iPhone customers don't buy just a phone; they buy into an experience enabled by the device. Similarly, Amazon.com customers enter a world of book reviews, interesting recommendations, instant downloads to their Kindle, and one-click purchasing. Products today are focal points, and it is the experience surrounding the product that matters the most. User Experience Innovation helps you create the right sort of experience around your products in order to be successful in the marketplace. The approach in User Experience Innovation is backed by 18 years of experience from an author holding more than 100 patents relating to user experience. This is a book written by a practitioner for other practitioners. You'll learn 17 specific methods for creating innovation; these methods run the gamut from targeting user needs to relieving pain points, to providing positive surprises, to innovating around paradoxes. Each method is one that the author has used successfully. Taken together, they can help you create truly successful user experience innovations to benefit your company or organization, and to help you grow as an experienced expert and innovator in your own right. Provides 17 proven methods for innovating around user experience Helps you think beyond the product to the sum total of a customer's experience Written by an experienced practitioner holding more than 100 user-experience patents